Complex brittle deformation pattern along the Southern Patagonian Andes (Argentina) - Barberon, Vanesa; Sue, Christian; Ronda, Gonzalo; Ghiglione, Matias
The Southern Patagonian Andes is located in the southern extreme of the Pacific subduction zone, where theAntartic oceanic plate sinks underneath South America. The history of the area begins with compression duringPaleozoic, Jurassic extension associated to the rift and opening of the South Atlantic Ocean, then a sag stage in theLower Cretaceous followed by a foreland phase as a result of plate tectonics (Ghiglione et al., 2016).The kinematic study is concentrated in the Argentinean foothills, between 46º40? and 48º SL.We measured around800 fault planes and their striaes with the sense of movement in order to characterize the stress field. The softwareused to make the stress inversion were Tensor (Delvaux, 2011) and Multiple Inverse Method MIM (Yamaji et al.,2011). The stress field map was built with the results of the MIM.We present new data from 48 sites located in the northern sector of the Southern Patagonian Andes. The measurementswere made in several rocks from Paleozoic to Lower Cretaceous, even though most were taken in pyroclasticjurassic rocks from El Quemado Complex. Paleostress tensors obtained are mostly strike-slip, although a 25% isnormal and there are a few compresional.The pattern of faults found is complex. In some sites the tensor can be locally linked to satellite images and observationsfrom the field or be related to a major thrust front. There is no clear correlation between the age and/orlithology with the tensor since the youngest rocks measured are Lower Cretaceous. Probably there are severalgenerations of family faults connected to different and recent tectonic phases then the paleostress tensors mightcorrespond to the latest tectonic events. Fil: Barberon, Vanesa. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: Sue, ...